2014
DOI: 10.1016/j.cellsig.2014.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the switches: Rho GTPase regulation during animal cell mitosis

Abstract: Animal cell division is a fundamental process that requires complex changes in cytoskeletal organization and function. Aberrant cell division often has disastrous consequences for the cell and can lead to cell senescence, neoplastic transformation or death. As important regulators of the actin cytoskeleton, Rho GTPases play major roles in regulating many aspects of mitosis and cytokinesis. These include centrosome duplication and separation, generation of cortical rigidity, microtubule-kinetochore stabilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 104 publications
(173 reference statements)
0
20
0
Order By: Relevance
“…RacGAP1 has a well-documented role in regulating cytokinesis (29,30), and ArhGAP11A has also recently been implicated in the control of this process (31). We therefore examined the effect of GAP-knockdown on the efficiency of BLBC cell division.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RacGAP1 has a well-documented role in regulating cytokinesis (29,30), and ArhGAP11A has also recently been implicated in the control of this process (31). We therefore examined the effect of GAP-knockdown on the efficiency of BLBC cell division.…”
Section: Resultsmentioning
confidence: 99%
“…In BLBC, we found that RacGAP1-depleted cells failed to proliferate as a result of cytokinesis failure, p21-induction, and the onset of senescence. The role of RacGAP1 in regulating cytokinesis is well-established (29,30) and, in BLBC, high levels of this protein may be required to facilitate excessive cell division. The GTPase specificity of RacGAP1 is controversial, with one study suggesting that this GAP could be converted from a Rac1- to a RhoA-specific GAP upon phosphorylation by aurora kinase B (50).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of Rho GTPase is stimulated by guanine nucleotide exchange factors (GEF) and inhibited by GTPase activating proteins (GAP) [1][2][3].…”
Section: Introductionsmentioning
confidence: 99%
“…Cyclin B is degraded as cells progress through anaphase towards the end of mitosis, leading again to the inactivation Cdk1 [25]. Mitotic Cdk1/cyclin B phosphorylates and regulates a myriad of key mitotic proteins, including the mitotic RhoGEFs Ect2, GEF-H1, and MyoGEF [26]. For example, phosphorylation of GEF-H1 by Cdk1, along with Aurora A kinase, during early mitosis inhibits GEF-H1, while dephosphorylation of GEF-H1, temporally coinciding with Cdk1 inactivation, prior to cytokinesis activates GEF-H1, thus promoting activation of RhoA [6].…”
Section: Introductionmentioning
confidence: 99%